2019
DOI: 10.1136/bmjspcare-2018-001734
|View full text |Cite
|
Sign up to set email alerts
|

Paramedics and serious illness: communication training

Abstract: ObjectivesThe need to empower Ambulance Service staff at the point of delivery of end of life care (EoLC) is crucial. We describe the delivery, outcomes and potential impact of the Serious Illness Conversation project delivered to Welsh Ambulance Service Trust (WAST) staff. Over an 18-month period, 368 WAST staff attended face-to-face teaching, which included serious illness conversation communication skills, symptom control and ‘shared decision making’.MethodData collected from WAST staff were used to gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Such disparity in guidelines have also been reported in the literature. 28 They faced rapid changes in their role in provision of EoLC, which some were not confident in, and while studies have previously reported this, [29][30][31][32][33] empowering staff at the point of delivery of EoLC has been deemed crucial and can make a real life impact. 30 The pandemic may have expedited developments in paramedic provision of EoLC and tragic decisions may have been made.…”
Section: Tragic Personal and Professional Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such disparity in guidelines have also been reported in the literature. 28 They faced rapid changes in their role in provision of EoLC, which some were not confident in, and while studies have previously reported this, [29][30][31][32][33] empowering staff at the point of delivery of EoLC has been deemed crucial and can make a real life impact. 30 The pandemic may have expedited developments in paramedic provision of EoLC and tragic decisions may have been made.…”
Section: Tragic Personal and Professional Choicesmentioning
confidence: 99%
“…28 They faced rapid changes in their role in provision of EoLC, which some were not confident in, and while studies have previously reported this, [29][30][31][32][33] empowering staff at the point of delivery of EoLC has been deemed crucial and can make a real life impact. 30 The pandemic may have expedited developments in paramedic provision of EoLC and tragic decisions may have been made. However, powerful positive EoLC encounters were reported by paramedics which may reflect professional and organisational growth which can emerge from such crises.…”
Section: Tragic Personal and Professional Choicesmentioning
confidence: 99%
“…Articles and blogs to help those less accustomed to technology have been written in response to the crisis. 23 , 25…”
Section: From a Hospital Palliative Care Perspectivementioning
confidence: 99%
“…Articles and blogs to help those less accustomed to technology have been written in response to the crisis. 23,25 This information, again with their consent, is shared on handover and referral forms, to enable community palliative care teams to have discussions. Some of these discussions will be challenging.…”
Section: From a Hospital Palliative Care Perspectivementioning
confidence: 99%
See 1 more Smart Citation